BLOOD GROUP ANTIGEN-DEPENDENT FEATURES OF POLYCLONAL IgE-RESPONSE IN CARBOHYDRATE METABOLIC DISORDERS - N. R. Telesmanich; M. A. Konovalchik; Z. I. Mikashinovich; E. G. Krivolapova (Медицинская иммунология)
Laboratory parameters of IgE-mediated immunological reaction (total IgE) were studied. Subjects with impaired carbohydrate metabolism and persons with diabetes mellitus were classified for blood groups 0(I), A(II), B(III) (n = 93). We determined total IgE, glucose levels and percentage of glycosylated hemoglobin (HbA1c) in blood serum; as well ABO blood groups. Comparison of these parameters in patient cohorts with 0(I) and A(II), B(III) blood groups showed different reactogenicity, depending on the degree of carbohydrate metabolism disturbance and ABO group specificity of antigenic determinants of blood glycoproteins. There was a strong direct correlation (r = 0.8) between blood group 0(I) antigens, and incidence of type 2 diabetes mellitus (DM). The highest correlation degree was observed between the blood group A(II) and type 1 diabetes onset of (r = 1.0). The smallest percentage of DM and the smallest correlation (r = 0.67) were observed in patients, B(III) blood group is located. In cases of sufficiently altered carbohydrate metabolism, the blood group 0(I) and A(II) carriers had total IgE of 43.61±15.12 kIU/L, and 86.2±42.61 kIU/L, respectively, thus being, on average, 4-times lower than in B(III) blood group in whom total IgE in type 2 diabetes was 2-fold higher than normal values, being 209.65±52.5 kIU/L.